(untitled) - Richards, Jack C. (New York, 2011)
Tactics for Listening Third Edition is an activity-rich listening course with proven success in building skills in listening and conversation. Now with Tactics for Testing, it provides plenty of practice in testing and exam techniques. The result is confident listeners - and exam success.
Nghe - Nói B1
Keywords: English language,Tiếng Anh; Sách giáo khoa cho người nước ngoài